Effect of pyrethroid pesticides on the testis of male rats: A meta-analysis. (April 2021) - Zhong, Mingqing; Zhai, Qingfeng; Zhang, Ruoyu; Yin, Haoyu; Li, Jiaxuan; Ma, Zhiyuan; Fang, Lei; Zhang, Chenyuan; Li, Yuanyuan
This study quantitatively evaluated the effects of pyrethroid pesticides on the testis of male rats. An extensive literature search for relevant studies was conducted on PubMed, Web of Science, Excerpta Medica Database, the Chinese National Knowledge Infrastructure, and Chinese Biomedical Literature Database. Pooled standard mean difference with corresponding 95% confidence interval was calculated via the random-effects model. I 2 was used to evaluate heterogeneity among studies. A total of 19 studies were included for analysis in our study. Results indicated that the sperm count of rats exposed to fenvalerate was lower than that of rats in control groups. The sperm count, sperm motility, and testosterone level of rats exposed to cypermethrin and deltamethrin were lower than those of rats in control groups. Moreover, the sperm morphology of rats exposed to these pyrethroid pesticides was abnormal compared with that of rats in control groups. The present meta-analysis indicates that pyrethroid pesticides decrease rat sperm count, sperm motility, and testosterone level and cause abnormal rat sperm morphology. Therefore, pyrethroid pesticides can damage the testis of male rats.